Simultaneous and Multiplexed Measurement of Curvature and Strain Based on Optical Fiber Fabry-Perot Interferometric Sensors - Chen Zhu; Hongkun Zheng; Osamah Alsalman; Wassana Naku; Lingmei Ma (Photonics, 2023)
Optical fiber sensors that have a compact size and the capability for multi-parameter sensing are desired in various applications. This article reports a miniaturized optical fiber Fabry-Perot interferometric sensor with a length of hundreds of µm that is able to simultaneously measure variations of curvature, temperature, and strain. The sensor is easy to fabricate, requiring only the fusion splicing of a short section of the silica capillary tube between two single-mode fibers (SMFs). The combined mechanism of the Fabry-Perot interference occurred in the two interfaces between the capillary and the SMFs, and the antiresonant guidance induced by the capillary tube makes the device capable of realizing multi-parameter sensing. A simplified coefficient matrix approach is developed to decouple the contributions from different parameters. In addition, the capability of the device for multiplexing is investigated, where four such prototypes with different air cavity lengths are multiplexed in a system in parallel. The spectral behavior of an individual device for measuring curvature and strain is reconstructed and investigated, showing reliable responses and little crosstalk between different devices. The proposed device is easy to fabricate, cost-effective, robust, and could find potential applications in the field of structural health monitoring and medical and human–machine interactive sensing.